INCOME ELASTICITIES OF DEMAND FOR MIDDLE AND LOW INCOME LIBYAN EMPLOYEES IN TRIPOLI - S. Mukerji, S. Mukerji (Dirasat in Economics and Business, 1968)
The present study is based on the data collected in the Family Budget Survey of Tripoli in 1962 1. The 1962 survey was primarily conducted to establish suitable weights for the calculation of a Cost of Living Index for a specific group of Libyan employees in Tripoli. However, the extensive set of tables provided in the report enables one to make some econometric studies. In this work an attempt has been made to estimate income elasticities of demand for food, housing, clothing, and miscellaneous items of consumer expenditure. The method adopted for analysis is similar to that given by Wold and Jureen 2. Field work for the Tripoli survey was completed within three months— 15th. January to 15th. April 1962. It may not, therefore, be very wrong to assume that the prices for the consumer goods remained constant throughout the period.